Private Lives, Public History: Navigating Historical Consciousness in Australia - Clark, Anna (History compass, 2016)
Contests over Australian history captivate governments, historians and public commentators; they grab headlines and spawn endless public commentary. The ‘history wars’, as those debates have come to be known, play out over museum exhibits, national commemorations, public apologies and the ways we teach the past to the next generation: should the Australian War Memorial commemorate the victims of the Australian frontier wars? Should Australians be sorry for historical actions in the past? Should Australian history be compulsory in school? (And so on.) But does that ‘national story’ have any meaning for Australian families and communities? This paper canvasses some recent qualitative research into historical consciousness in Australia to explore the ways those historical discourses operate beyond the public domain. It asks participants to speak in their own words about what history means: how they relate to their local and family histories, and how they engage with Australian history more broadly. Importantly, the project reveals a depth and complexity to Australians' historical engagement and demonstrates that public and personal discourses about the past do indeed intersect in everyday life around the country.